2017
DOI: 10.1002/pds.4339
|View full text |Cite
|
Sign up to set email alerts
|

Being overweight or obese as a risk factor for acute liver injury secondary to acute acetaminophen overdose

Abstract: Purpose: Increased incidences of hepatotoxicity have been observed in obese patients with acute acetaminophen overdose. We evaluate whether the status of being overweight or obese is associated with increase in the development of hepatotoxicity and acute liver injury (ALI) in patients with acute acetaminophen overdose.Methods: This was a retrospective cohort study comparing the risk of hepatotoxicity and ALI between overweight or obese patients (body mass index [BMI] ≥ 25) and normal BMI patients (BMI ≤ 24.9) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
0
20
1
Order By: Relevance
“…Furthermore, there are adverse effect concerns when increasing doses beyond those needed to reach the analgesic ceiling effect [27][28][29]. Some adverse effects (e.g., acetaminopheninduced liver injury) may be more frequent in patients with obesity [30,31]. Therefore, no size descriptor recommendation is needed for analgesic agents administered by non-weight-based dosing regimens.…”
Section: Non-opioid Analgesicsmentioning
confidence: 99%
“…Furthermore, there are adverse effect concerns when increasing doses beyond those needed to reach the analgesic ceiling effect [27][28][29]. Some adverse effects (e.g., acetaminopheninduced liver injury) may be more frequent in patients with obesity [30,31]. Therefore, no size descriptor recommendation is needed for analgesic agents administered by non-weight-based dosing regimens.…”
Section: Non-opioid Analgesicsmentioning
confidence: 99%
“…For a more detailed assessment of the risk factors for hepatotoxicity, and in view of the fact that a considerable proportion of patients presented with a moderate increase in plasma aminotransferase levels (over the normal range but below 1000 IU/L), we divided the study population into three groups, as described above. In the available literature, there are numerous studies that have discussed new risk factors for hepatotoxicity [ 9 , 10 , 11 , 15 , 16 , 19 , 20 , 21 , 22 , 23 , 24 ], including parameters related to the patient’s medical history, acetaminophen dose, biochemical findings, or a combination thereof. Quantitative and qualitative medical variables, which might serve as such risk factors in the studied population, are presented in Table 1 and Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…In both animal and human studies, diabetes mellitus is an independent risk factor for severe DILI outcomes . For example, one recent study demonstrated that overweight or obese patients were more likely to develop acetaminophen hepatotoxicity .…”
Section: Demographics Of Patients With Severe Dilimentioning
confidence: 99%
“…22 In both animal and human studies, diabetes mellitus is an independent risk factor for severe DILI outcomes. 19,[23][24][25] For example, one recent study demonstrated that overweight or obese patients were more likely to develop acetaminophen hepatotoxicity. 23 In addition, a recent study of 259 patients with inflammatory bowel disease receiving immunosuppressants demonstrated that those with baseline steatosis were more likely to develop liver injury.…”
Section: Demog R Aphi C S Of Patients With S E Vere D Ilimentioning
confidence: 99%
See 1 more Smart Citation